The Efficacy of Treatment of Hemangiomas in Infants with Nonselective β-Blockers (Propranolol) - Kuzyk A. (Львівський клінічний вісник)
Introduction. Hemangiomas – are tumorlike vessel changes that occur in children starting from an early age and can appear as minor cosmetic defects that sometimes spontaneously decrease, or can cause serious functional disorders or even be a threat to life. As of today the choice of treatment strategy remains controversial. All the methods for the treating of hemangiomas are divided into local (surgical treatment, laser ablation, selective endovascular embolisation) and systemic (corticosteroids, interferon α2a, cytostatics, procoagulants) treatment with a possible combination. However, these methods are not universal and can not always eliminate the threat to life or disability. In 2008, the first results were published on the use of propranolol in the treatment of hemangiomas in young children, which was the beginning of revolutionary changes in the views of the tactics of treatment of one of the most common pathologies of childhood. Aim. To find out the effectiveness of conservative treatment of hemangiomas with non-selective β-blocker (propranolol) in young children. Materials and methods. In this prospective study we have analyzed the effectiveness of treatment of hemangiomas in 43 children at the age 2–19 months with propranolol (daily dose of 1.0-4.0 mg/kg body weight, divided into three doses, with a tendency to hold the dose in the range of 2.0-3.0 mg/kg/day). 28 patients had isolated hemangiomas of the head and neck area. Treatment lasted from 2 to 14 months and is completed in 33 patients. Results. The presence of hemangiomas in early childhood in the phase of proliferation, especially complicated, leading to impairment of vital functions or to the persistent disturbances and significant negative cosmetic effects, is an indication for systemic treatment. The vast majority of patients (41 children) received a positive clinical response: tumor growth stopped, followed by a decrease of it size up to extinction of the tumor with the absence of significant complications. In the vast majority of patients, since the first days of treatment, a positive reaction of hemangiomiomas was observed as a change in color (weakening), diminishing its tension. This tendency was maintained with the highest intensity during the first months of treatment. No violations of the cardiovascular system or glycemic index were detected. In no patient, the side effects were not a reason for the discontinuation of the treatment. These results indicate the high efficiency of treatment together with its good tolerance, high availability and low risk of complications. Conclusions. An early evaluation of the effectiveness of treatment of hemangiomas with non-selective β-blocker propranolol suggests its high efficacy with simultaneous good tolerance.